Prehistoric fires in the Chirripó highlands of Costa Rica: Sedimentary charcoal evidence - P. Horn, Sally (1989)
To determine the long-term history of fire in the Chirripó highlands of Costa Rica, the charcoal content of a 110 cm sediment core from a glacial lake was analyzed. The core was raised from Lago Chirripó, the largest of the approximately thirty glacial lakes in the Chirripó massif. The basal sediments from the core yielded a radiocarbon date of 4110 yr. B.P. The charcoal record indicates that the watershed of the lake has burned repeatedly during the past four thousand years due to human activity, lightning, or both.